IgY anti - Trypanosoma cruzi - produção e avaliação imunoterápica - Grando, Thirssa Helena (2018)
Trypanosoma cruzi, the etiological agent of Chagas disease, is a flagellate protozoan belonging to the family Trypanosomatidae. Chagas disease is one of the main public health problems in Brazil and Latin America, and therefore there is a need for research to control this disease, since the existing chemical treatment is long, produces side effects and is not always effective. The name IgY, refers to egg yolk immunoglobulin (Y = yolk) and the production and use of this avian antibody has been studied by several researchers because of the diversity of diagnostic and therapeutic applications. Research has shown that the use of specific IgY prevents and controls infectious and parasitic diseases. Knowing that the treatment of Chagas disease requires new alternatives, this research aimed to produce and evaluate the therapeutic efficacy of specific avian antibodies against Trypanosoma cruzi. Firstly, chickens were immunized with trypomastigotes of T. cruzi (strain Y) for the production of effective and specific IgY antibodies, which were extracted, characterized, quantified and analyzed for their cytotoxic effect. After obtaining the anti-T cruzi IgY, the therapeutic efficacy of specific avian polyclonal antibodies (IgY) against Trypanosoma cruzi and its interaction with ecto-enzymes of the purinergic system (NTPDase and adenosine deaminase (ADA) activities) in splenic lymphocytes. To this end, mice were experimentally infected with T. cruzi (strain Y) treated with IgY - anti T. cruzi at a dose of 50mg / kg in two protocols, one prophylactic (before and during infection) and one therapeutic (after infection). The results of this study demonstrated that T. cruzi was able to generate in chickens an excellent production of specific immunoglobulins. In cytotoxic assays, Igy did not cause damage to the cell membrane and its proliferative effect. In the in vivo study, the therapeutic use of IgY - anti T. cruzi decreased the invasion of the parasites in the cardiac cells in the acute phase and improved the immune and inflammatory response of the mice infected experimentally by T. cruzi. These results show that Igy - anti T. cruzi immunotherapy may be considered as a tool for the control and treatment of Chagas' disease, requiring further studies in other animal species, duration of treatment and tests with different immunotherapeutic concentrations.